PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA, KEMAMPUAN PENALARAN DAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA BAGI SISWA KELAS X MAN 1 KOTA BENGKULU - Rita Sartika (Jurnal Pendidikan Matematika Raflesia, 2017)
The purpose of this study was conducted to determine the effect of Problem Based Learning aided interactive learning media on the ability of understanding the concepts, communication skills and mathematical reasoning abilities in the class X IPS MAN 1 City of Bengkulu. This research is quasi experiment research. The data collection is done by using a test sheet reasoning ability, the ability of understanding the concept and communicationskills. The results showed that the influences of the problem based learning model of interactive learning media aided the understanding of the concept of mathematical ability of students by 34.8%. There is the influence of problem based learning model of media-aided interactive learning to students' mathematical communication skills by 45,2 %. There is the influence of problem based learning model of media-aided interactive learning to students' mathematical reasoning abilities by 45%. There is a problem based learning model of the effect on the ability of students' mathematical reasoning by 42,5%. There is a model of the effect of problem based learning to the students' mathematical communication skills by 25.8%. There is a problem based learning model of the effect on the ability of students' understanding of mathematical concepts by 22.5%. There is the influence of the application of conventional learning aided interactive learning media on mathematical communication skills by 15,78 %. Effect of the application of conventional learning aided interactive learning media on mathematical reasoning  skills was 24,89 %. Effect of the application of conventional learning aided interactive learning media on mathematical understanding the concepts was 16,74%. Keywords:  problem based learning, interactive learning media, mathematical communication, understanding the concept, mathematical reasoning.